2008
DOI: 10.1007/s11154-008-9090-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and diabetic retinopathy: Pathophysiological mechanisms and treatment perspectives

Abstract: Retinopathy is one of the most severe ocular complications of diabetes and is a leading cause of acquired blindness in young adults. The cellular components of the retina are highly coordinated but very susceptible to the hyperglycemic environment. The microvasculature of the retina responds to hyperglycemic milieu through a number of biochemical changes, including increased oxidative stress and polyol pathway, PKC activation and advanced glycation end product formation. Oxidative stress is considered as one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
195
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(204 citation statements)
references
References 139 publications
1
195
1
7
Order By: Relevance
“…155 Consumption of dark chocolate is associated with blood pressure reduction associated with a reduction in oxidative stress and increase in nitric oxide bioavailability, 156 both abnormalities that have been involved in the pathogenesis of diabetic nephropathy and retinopathy. 67,[85][86][87][88][93][94][95][97][98][99]156 Finally, in experimental diabetes, the use of green tea was associated with an improvement in diabetic nephropathy and retinopathy and associated with a reduction in oxidative stress. 91, 157 The usefulness of these dietary approaches in diabetic patients with hypertension and nephropathy or retinopathy that are on standard treatment deserves to be tested in larger clinical trials.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…155 Consumption of dark chocolate is associated with blood pressure reduction associated with a reduction in oxidative stress and increase in nitric oxide bioavailability, 156 both abnormalities that have been involved in the pathogenesis of diabetic nephropathy and retinopathy. 67,[85][86][87][88][93][94][95][97][98][99]156 Finally, in experimental diabetes, the use of green tea was associated with an improvement in diabetic nephropathy and retinopathy and associated with a reduction in oxidative stress. 91, 157 The usefulness of these dietary approaches in diabetic patients with hypertension and nephropathy or retinopathy that are on standard treatment deserves to be tested in larger clinical trials.…”
Section: Discussionmentioning
confidence: 97%
“…92 Further corroborating the contribution of hypertension to retinal damage in diabetic SHR, we have demonstrated that anti-hypertensive treatment either with losartan (an AT1 receptor blocker, ARB) or with triple therapies (hydralazine, reserpine and hydrochlorothiazide) abolished these effects. 84 In the retina, a number of studies have shown that there is an increase in oxidative markers after the induction of DM, 67,[93][94][95] but the concomitance of diabetes and hypertension evoked earlier oxidative retinal damage characterized by an increase in nitrotyrosine and 8-OHdG in retinal tissue from short-term STZ-induced DM in SHRs. [96][97][98][99] These oxidative markers were the consequence of an increase in superoxide production and depletion of the gluthationereduced antioxidant system in the retinal tissue.…”
Section: Inflammation and Oxidative Stress As The Underlying Mechanismentioning
confidence: 99%
“…7 Globally, DM is the leading cause of blindness, especially in developing countries. 8,9 Hyperglycemia, glycation of hemoglobin, and duration of diabetes disease are among multiple factors involved in the development of diabetic retinopathy (DR). 9,10 In addition, retinal ischemia and OS are important processes in developing DR. Of much importance, it has been reported that hyperglycemia per se lead to increased generation of FRs and OS.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Hyperglycemia, glycation of hemoglobin, and duration of diabetes disease are among multiple factors involved in the development of diabetic retinopathy (DR). 9,10 In addition, retinal ischemia and OS are important processes in developing DR. Of much importance, it has been reported that hyperglycemia per se lead to increased generation of FRs and OS. 11,12 The status of OS in health and disease is determined by an array of oxidative damage markers and antioxidant defense systems.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable experimental evidence, generated in both tissue culture and animal models, indicate that in diabetes, retinal cells undergoes accelerated apoptosis and induces acellular capillaries and pericyte ghosts in retinal vasculature by unknown mechanism [12][13][14]. Over the last several years, multiple mechanisms on the altered cell signaling pathways and its components, including oxidative stress and polyol pathway, protein kinase C (PKC), and mitogen-activated protein kinases (MAPK) in the microvasculature of the diabetic retina have been shown [15][16][17][18][19][20][21][22][23]. Understanding on such mechanistic pathways might help to develop future adjuvant therapies for diabetic retinopathy.…”
mentioning
confidence: 99%